An examination of the determinants of performance in relation to the divestiture of state-owned assets in China : a thesis presneted in fulfilment of the requirements for the degree of Doctor of Philosophy - Liao, Jing (Massey University, 2010)
Compared with other countries, China’s privatization has not been fully successful, as profitability decreased following share issue privatization. This thesis focuses on two features that affect post-privatization performance in China: regional disparity and the inefficiency of board structure. It is argued that privatization does not mean just the transfer of ownership from the State to the private sector, but the combination of such ownership transfer with deregulation and the injection of domestic and foreign competition, as well as institutional changes. It is shown that performance varies with the extent of regional development proxies in China. In particular, the injection of foreign competition is significantly and positively related to Tobin’s Q. On August 16, 2001, the China Securities Regulatory Commission (CSRC) issued the “Guidelines on Establishing an Independent Director System in Listed Companies” to protect small shareholders from expropriation by dominant shareholders. It has been noted that under the highly concentrated ownership structure and insider-dominated boards of listed firms, independent directors cannot work efficiently as monitors in China. Besides satisfying the government and signalling the market, the main contribution of independent directors is to provide advice to top management. The results of this thesis show that large and diversified firms prefer larger boards with more independent directors; moreover, for large and diversified firms, Tobin’s Q increases with board size and board independence. iv It is found that Chinese-listed firms exhibit two types of connections provided by independent directors: 43.76% of the independent directors are university scholars or researchers, and 13.88% of them are politically connected. The empirical results show that the relationship between Tobin’s Q and the presence of scholars and politically connected outsiders on a board is significantly negative. But it has been found that scholars, commercial bankers, and politically connected independent directors can add value to large firms, highly leveraged firms, and firms without politically connected CEOs, respectively. Moreover, it is found that the recruitment of independent directors does not limit the related party transactions between the listed companies and their controlling shareholders.
Keywords: Privatisation; State ownership; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management